Submitted as a Partial Fulfillment of the Requirements for Getting Master Degree of Education in Educational Management Department - Lukmawati, Isti (2011)
The objectives of this research are to describe (1) the syllabus preparation characteristics of the Central Elementary School at Elementary School Kalisari I Sayung Demak. (2) lesson plan preparation characteristics of the Central Elementary School at Elementary School Kalisari I Sayung Demak. (3) teaching material characteristics of the Central Elementary School at Elementary School Kalisari I Sayung Demak. It is a qualitative research using ethnography design. This research was conducted at Elementary School Kalisari I Sayung Demak. The main subject in this research was the principal, and teachers of Elementary School Kalisari I Sayung Demak. Data collection method used was interview, observation, and documentation. Data analysis was started with (1) Collecting Data, (2) Data Reduction, (3) data display, and (4) drawing conclusion. Data validity test used credibility, transferability, confirmability, and dependability. The results of this research are (1) the preparation of the central elementary school syllabus in Elementary School Kalisari I Sayung Demak is held in KKG (Teacher's Working Group) forum every Saturday (seton). Elementary School Kalisari I formed the ninth team to prepare the syllabus. The document prepared are standard of competence, basic competence, education calendar, syllabus writing format, source books and supporting stationary. Before being duplicated and delivered to other impact elementary schools, the syllabus preparation has a revision and stabilization steps by the school. (2) The Central Elementary School lesson plan in Elementary School Kalisari I Sayung Demak is prepared well through outlining the syllabus that has been determined previously. The components prepared include elevent components namely the preparation of subject identity, standard of competence, basic competence, indicator, learning goals, time allocation, material, learning methods, learning activities, learning outcome assessment, and source of material. The Nationalism material is the special material prepared by Elementary School Kalisari I in preparing the lesson plan. The lesson plans is focused on students where the preparation is tailored to students. (3) Teaching materials of the central elementary school at Elementary School Kalisari I Sayung Demak are prepared based on the standard of competence and basic competence that has been determined. The preparation focused on the standard of competence and basic competence, students' activity, infrastructure, and environment. Teaching materials delivered using simple props and ICT-base media. Sources of materials are from electronic media, printed media and environment. The principal invited the expert from outside the school such as Mr. Sahri to give input and evaluate it.